2002
DOI: 10.1159/000066748
|View full text |Cite
|
Sign up to set email alerts
|

Hindbrain and Cranial Nerve Dysmorphogenesis Result from Acute Maternal Ethanol Administration

Abstract: Acute exposure of mouse embryos to ethanol during stages of hindbrain segmentation results in excessive cell death in specific cell populations. This study details the ethanol-induced cell loss and defines the subsequent effects of this early insult on rhombomere and cranial nerve development. Ethanol at a teratogenic dosage (2.9 g/kg) or a comparable volume of vehicle was administered in each of two intraperitoneal injections to pregnant C57BL/6J mice on gestational day (GD) 8, 8 h, and GD 8, 12 h (defined he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 60 publications
9
85
0
Order By: Relevance
“…We have previously demonstrated that apoptosis (cell death) can be visualized in 8-9 days old mouse embryos, rat fetal limbs, and other tissues using a fluorescent dye (LysoTracker Red, LT), which stains lysosomes and acidic regions of cells/tissues (16)(17)(18)(19)(20)(21)(22)(23). The current study extends our previous work to visualize apoptosis within follicles of a whole ovary (17).…”
supporting
confidence: 66%
See 2 more Smart Citations
“…We have previously demonstrated that apoptosis (cell death) can be visualized in 8-9 days old mouse embryos, rat fetal limbs, and other tissues using a fluorescent dye (LysoTracker Red, LT), which stains lysosomes and acidic regions of cells/tissues (16)(17)(18)(19)(20)(21)(22)(23). The current study extends our previous work to visualize apoptosis within follicles of a whole ovary (17).…”
supporting
confidence: 66%
“…From previous studies on embryos, the appearance of LT in tissue is strongly suggestive of apoptosis (16)(17)(18)(19)(20)(21)(22)(23). The LT has a fluorescence peak at 610 nm (Leica SP1), while the AIF has a fluorescence peak around 471 nm with UV or cyan GFP excitation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Four nuclei affected by ethanol exposure during gastrulation include three trigeminal nuclei (the PSN, SpVo, and MoV) and the MoVII. These changes in the brainstem occur after an exposure to ethanol that is associated with FAS-like craniofacial malformations (Sulik et al, 1981;Astley et al, 1999;Dunty et al, 2002;Da Lee et al, 2004). In addition, four nuclei (the MoV, MoVII, MoXII, and PSN) are affected by ethanol exposure during neuronal generation.…”
Section: Timing Of the Ethanol-induced Vulnerabilitymentioning
confidence: 99%
“…One critical window of ethanol vulnerability coincides with the period of gastrulation. In mice, exposure to ethanol on gestational day (G) 7 or G8 increases the expression of markers for cell death (Dunty et al, 2002;Kilburn et al, 2006). More impressive is that mice exposed to ethanol during gastrulation (Sulik et al, 1981;Dunty et al, 2002;Da Lee et al, 2004) exhibit craniofacial malformations like those that characterize human children with fetal alcohol syndrome (FAS) (Lemoine et al, 1968;Jones and Smith, 1973).…”
Section: Introductionmentioning
confidence: 99%